Theory of mind and general intelligence in dictator and ultimatum games - Hannes Lang; Gregory DeAngelo; Michelle Bongard (Games, 2018)
Decreasing social sensitivity (i.e., the ability of a person to perceive, understand, and respect the feelings and viewpoints of others), has been shown to facilitate selfish behavior. This is not only true for exogenous changes in social sensitivity, but also for social sensitivity influenced by someone's social cognition. In this analysis, we examined one measure of social cognition, namely a person's Theory of Mind (ToM), to examine differences in decision-making in standard non-strategic and strategic environments (dictator and ultimatum games). We found that participants with higher ToM gave a greater share in the non-strategic environment. In the ultimatum game, however, ToM showed no correlation with the offers of the ultimators. Instead, we found that general intelligence scores-measured by the Wonderlic test-shared a negative, albeit weak, correlation with the amount offered in the ultimatum game. Thus, we find that lower social cognition is an important explanatory variable for selfish behavior in a non-strategic environment, while general intelligence shares some correlation in a strategic environment. Similar to the change in social sensitivity created by a specific game design, social sensitivity influenced by individual personality traits can influence behavior in non-strategic environments.
Keywords: 330; dictator game; ultimatum game; theory of mind; intelligence; experiment